PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KIMIA PESERTA DIDIK KELAS XI MIPA 4, SEMESTER GANJIL, SMA NEGERI 2 MENGWI TAHUN PELAJARAN 2019/2020 - Ni Nyoman Sunetri (Widyadari : Jurnal Pendidikan, 2021)
The low and the result of chemistry subject of grade eleven of science 4 where the average for it only 60. The problem of this research is "does inquiry teaching model Can improve to all student of grade eleven science 4 on first semester year 2019/2020 at Badung regency. is it possible to apply this inquiry teaching model can improve the motivation of the student result of chemistry subject of grade eleven science 4 on first semester year 2019/2020. The result of the research shows that applying inquiry teaching model can improve the student activity when learning chemistry subject of grade eleven science 4 on first semester of SMA Negeri 2 Mengwi year 2019/2020 at Badung regency that have known by the positive response of the student on first cycle can be reach 38,59 and increase on second cycle 40,12. Applying this inquiry teaching model can improve the activities of the student and the result of chemistry subject of grade eleven of science 4 of SMA Negeri 2 Mengwi year 2019/2020 at Badung regency, this is the best way to improve student activities on teaching learning process by using inquiry model.